Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Pelaku E-Commerce di Kabupaten Lamongan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the factors that influence taxpayer compliance of e-commerce actors in Lamongan Regency. The independent variables used in this study include tax socialization, taxpayer awareness, tax understanding, and tax rates. The dependent variable in this study is taxpayer compliance. This study uses a descriptive quantitative approach with a survey method. Primary data were collected through questionnaires distributed to e-commerce business actors who were the research samples. The data analysis technique used multiple linear regression to determine the partial and simultaneous effects of each independent variable on the dependent variable. The results of the study indicate that partially, tax socialization, taxpayer awareness, and tax understanding have a significant effect on taxpayer compliance. Meanwhile, tax rates do not show a significant effect partially. However, simultaneously, the four variables have a significant effect on taxpayer compliance. This finding implies that increasing tax compliance in e-commerce actors can be encouraged through optimizing socialization, increasing awareness, and understanding of taxation, as well as evaluating applicable tax rate policie.